2007
DOI: 10.1111/j.1471-4159.2007.04894.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NCAM‐binding peptides promoting neurite outgrowth via a heterotrimeric G‐protein‐coupled pathway

Abstract: A combinatorial library of undecapeptides was produced and utilized for the isolation of peptide binding to the fibronectin type 3 modules (F3I-F3II) of the neural cell adhesion molecule (NCAM). The isolated peptides were sequenced and produced as dendrimers. Two of the peptides (denoted EN-FIN2 and ENFIN11) were confirmed to bind to F3I-F3II of NCAM by surface plasmon resonance. The peptides induced neurite outgrowth in primary cerebellar neurons and PC12E2 cells, but had no apparent neuroprotective propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…1 D). Neurons were transfected with either a plasmid encoding shRNA for NCAM or control shRNA (Hansen et al, 2007). To confirm the knockdown of NCAM expression, the transfected neurons were stained for NCAM.…”
Section: Gdnf Induces Differentiation Of Hippocampal Neurons Via Ncammentioning
confidence: 99%
See 2 more Smart Citations
“…1 D). Neurons were transfected with either a plasmid encoding shRNA for NCAM or control shRNA (Hansen et al, 2007). To confirm the knockdown of NCAM expression, the transfected neurons were stained for NCAM.…”
Section: Gdnf Induces Differentiation Of Hippocampal Neurons Via Ncammentioning
confidence: 99%
“…A vector encoding short hairpin RNA (shRNA) for NCAM (Hansen et al, 2007) was used to knock down the expression of NCAM. A vector encoding shRNA not targeting any known expressed rat sequence (Hansen et al, 2007) was used as a control.…”
Section: Transfection Of Hippocampal Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IF and biochemical analyses indicated that FGFR in cells stimulated by NCAM is channeled to a recycling pathway back to the cells surface. After 60 min of treatment, FGFR in FGF-treated cells was found in lysosomes, whereas those by NCAM were in the recycling endosome compartment and exhibited with its FNIII domain induced neurite outgrowth through a pathway that involves heterotrimeric G proteins, and that is independent of FGFR and Fyn (Hansen et al 2007). The above illustrates the complex diversity in NCAMassociated signaling.…”
Section: Introductionmentioning
confidence: 97%
“…L1 converges with NCAM signaling upstream of the MAPK pathway at the level of Raf (18,21,28,29). NCAM may induce alternative signaling pathways, including protein kinase A-dependent signaling or G-proteins (18,30). NCAM signaling to the nucleus may include activation of CREB and c-Fos or NF-B (29,31,32).…”
mentioning
confidence: 99%